Comparison of the injection of low‐molecular weight heparin in the arterial vs. venous blood line for preventing extracorporeal circuit clotting during hemodialysis. Issue 3 (10th January 2022) - Belmouaz, Mohamed; Goussard, Guillaume; Joly, Florent; Grand, Francois; Sibille, Audrey; Ecotiere, Laure; Desport, Estelle; Bauwens, Marc; Thierry, Antoine; Bridoux, Frank
Abstract: Low‐molecular weight heparins (LMWH) are widely used for preventing clotting during hemodialysis (HD). Although injection in the venous blood line is recommended to avoid initial loss of LMWH through the dialyzer, LMWH is still frequently administered in the arterial blood line at the start of dialysis. This study aimed to compare the safety and efficacy of the same enoxaparin dose administered through the venous blood line or arterial blood line. We also evaluated antifactor Xa (aXa) activity according to the injection route and dialysis modalities: high‐flux (HF) HD, medium cut‐off (MCO) HD, and online hemodiafiltration (OL‐HDF). Forty‐three patients were studied over 18 consecutive dialysis sessions using a fixed enoxaparin dose (20 or 40 mg), first administered through the arterial blood line bolus and then through the venous blood line for another 18 sessions. Compared to arterial blood line administration, venous blood line bolus resulted in a significant increase in median post‐dialysis aXa activity: 0.16 (0.1–0.6) IU/ml versus 0.31 (0.1–1.3) IU/ml, respectively, p = 0.006. After arterial blood line bolus of 40 mg enoxaparin, median post‐dialysis aXa activity was significantly lower with OL‐HDF compared to HF‐HD: 0.14 (0.1–0.35) versus 0.32 (0.15–0.49), p = 0.02. A trend for lower clotting within lines and bubble trap using venous blood line bolus was observed. In conclusion, venous blood line enoxaparin injection is safe in OL‐HDF patients. However, in HF‐HD and MCO‐HD, venous blood line injection of 40 mg enoxaparin may increase overdosing risk. Thus, aXa activity should be monitored in HF‐HD and MCO‐HD patients at risk of bleeding and/or on vitamin K antagonists and careful surveillance is required when administering a 40 mg enoxaparin dose through the venous blood line route.